(untitled) (London Journal of Research In Humanities and Social Sciences, 2024)
The impression we have that we are in the future, but we think with the mind of the past. Not only for the war of the last Tsar of Russia, which shakes the remains of the post-Soviet empire but also for the religious war in the Middle East. Our world is also marred by other wars in Africa, in the Caucasus, in ex-Soviet Asia but they are conflicts of an economic nature for the control of the great resources of the black continent. Thus defined the geopolitical framework, the current horizon is clarified, and the gaze is freed for the near future. Because, as in the times of the Homeric wars, what is up for grabs is the economy and the coordination of growth to accelerate common development. There is an urgent need for humanity to free itself from the constraints that hinder progress yesterday and today. First, dedicate large resources to changing the resources we can use as energy, to restore good relations between humanity and the planet that welcomes us. It is not enough. Because the potentials in the West and East are blocked by laws of nature, such as inflation and deflation, monetary anomalies that slow down development and excite old grudges and ideas from the past. We can get rid of the monetary anomalies that excite selfishness (speculation) and return to constant and coordinated development. In fact, the objective of accelerating coordinated development as a whole is certainly important, as opposed to today’s messy situation, with countries lagging behind on the path to progress and civilization. The perspective is already underway although, due to the myopia that distinguishes us, it is not fully perceived. The sign of novelty comes from the social and economic tensions that have allowed the creation of supranational bodies, starting with the UN and the planned and ongoing continental unions which indicate the way to finally relegate the very idea of wars and conflicts to the history books. With the angle from the economic side, the tense relations between the West and China can be simplified. The problems of the economy do not absolve anyone. Let’s consider that half the world is in the grip of deflation and the other half is in the grip of inflation. All of us, and together, we must face the planet’s malaise and the coordination of development between continents. A reality awaits us where science is destined to overcome the value of money and, at the same time, to change social values.